Multivariate analysis between environmental factors and fruit quality of citrus at the core navel orange-producing area in China - Yu, Xiaoxuan; Du, Chao; Wang, Xiaojun; Gao, Fengying; Lu, Jing; Di, Xinyue; Zhuang, Xia; Cheng, Chen; Yao, Fengxian (Frontiers in Plant Science, 2024)
Gannan is the largest navel orange production area in China. Most studies have primarily focused on the effects of either soil or topographic factors on the quality of navel oranges. However, there has been a lack of research exploring the relationship between navel orange quality and multiple environmental factors (meteorological, topographic, and soil). This study focused on Gannan navel oranges, selecting standard orchards in the core navel orange-producing area as the research region. It employed the Partial Least Squares Regression (PLSR) method to investigate the extent of the impact of environmental factors on fruit quality. The results indicated that the effect of soil factors on fruit shape and fruit flavor was greater than that of meteorological and topographic factors in the Gannan area. And the fruit peel is more uniformly influenced by environmental factors. Based on the degree of impact of various environmental factors, multiple regression equations for fruit quality have been established to identify the optimal conditions conducive to the comprehensive development of Gannan navel oranges. These findings help determine the optimal planting areas for Gannan navel oranges, providing practical evidence for the future development of navel oranges.